Headache and Psychiatric Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Headaches and psychopathology were evaluated in 1013 children, aged 9 to 15 years, enrolled in the Great Smoky Mountains Study, and reported from Duke University Medical Center, Durham, NC.